Analisis Purchasing Power Parity Indonesia Menggunakan Pendekatan Error Correction Model - Aula Ahmad Hafidh (Universitas Negeri Yogyakarta, 2005)
This papers tests for Purchasing Power Parity (PPP) between Indonesia and its main trading partner United States (US) using Error Correction Model (ECM). We examine the mean-reverting properties of real exchange rates. The tests shows that PPP is hold underlying the theory, purchasing power relationship is shown to exist. The model is, furthermore, shown to have significant forecasting power